VIBRIOSIS OUTBREAK IN PRAWN FARMS AND THE GROWTH THRESHOLD OF ENDEMIC PATHOGENS POPULATION - SHYAMALA, D.R.; RAMALNGAM, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Mass mortality among cultured tiger praws (Penaeus monodon) due to vibriosis was a common occurrence in summer months in the south-east coast of India. The Vibrio species were isolated and identified through culture from the diseased shrimps. A one-year field survey on the presence of Vibrio species in P. monodon was carried out in about 15 commercial farms around Madras by a conventional culture method. The results revealed that the pathogen is widely distributed in the prawn culture environment. Its population, which increases with the rise in temperature during summer months, is implicated for the mass mortality of the prawns. The Vibrio strains isolated from the tissues of diseased prawns were cultured in TCBS agar. The strains identified were V parahaemolyticus and V. aginolyticus.